PENGARUH TOTAL QUALITY MANAGEMENT TERHADAP KINERJA KARYAWAN PADA PT SULING MAS TRI TUNGGAL ABADI - Jonathan Ristian; Fitri Novika Widjaja; Antonius Budhiman Setyawan (CALYPTRA, 2019)
Abstract - This study aims to determine the effect of Total Quality Management (TQM) simultaneously and partially on employee performance of PT Suling Mas Tri Tunggal Abadi. This research uses a quantitative approach with simple linear regression analysis method. The samples used are employees who have subordinates such as managers and supervisors. The number of samples that used in this study were 55 employees. The results showed that there is a strong relationship between the application of TQM with employee performance in PT. Suling Mas Tri Tunggal Abadi. Total Quality Management (TQM) proved to affect the employees simultaneously and partially on the PT. Suling Mas Tri Tunggal Abadi.